A systematic review and meta-analysis of salmonellosis in poultry farms in Ethiopia: prevalence, risk factors, and antimicrobial resistance - Basazinew, Eyoel; Dejene, Haileyesus; Dagnaw, Gashaw Getaneh; Lakew, Asres Zegeye; Gessese, Abebe Tesfaye (Frontiers in Veterinary Science, 2025)
Salmonellosis has a significant impact on the chicken production industry and is becoming a serious threat to public health. However, there is no systematic and inclusive report on the prevalence, associated risk factors, and antimicrobial resistance of chicken salmonellosis in Ethiopia. Therefore, the objective of this study was to estimate the pooled prevalence, identify possible risk factors, and assess antimicrobial resistance of Salmonella in poultry farms across Ethiopia. Studies were identified from databases such as Medline/PubMed, ScienceDirect/Scopus, Google Scholar, Web of Science, and Science Pub. The overall literature review and quantitative synthesis were conducted following the PRISMA guidelines. Overall, data extraction was conducted using Microsoft Excel, and statistical analysis was performed using R software. A total of 12 articles, published between August 2017 and October 2024, were included in the final quantitative synthesis. A random-effects meta-regression model was employed to estimate the pooled prevalence. The overall pooled prevalence of poultry salmonellosis was 12.46% (95% CI: 8.44, 16.48), with high heterogeneity (I2 = 97%, τ2 = 0.0041, p < 0.01). The subgroup meta-analysis of the study area showed that the prevalence proportion was higher in western Ethiopia, at 23.18% (95% CI: 8.96–37.39%). Based on the purpose of production, the highest pooled prevalence was observed in broilers at 28.23% (95% CI: 19.97–36.49%), while the highest prevalence based on age was in poultry under 6 months, at 14.45% (95% CI: 8.92–19.99%). Additionally, higher prevalence proportions were observed in local breeds and the Cobb 500 variety, with prevalence rates of 39.78% (95% CI: 19.50–60.06%) and 45.26% (95% CI: 23.44–67.08%), respectively. The highest pooled resistance levels for antimicrobials were observed against tetracycline (75%) (95% CI: 70–79%) and oxytetracycline (64%) (95% CI: 56–71%), while the lowest pooled resistance levels were against cefotaxime (3%) (95% CI: 0–7%) and gentamycin (6%) (95% CI: 4–9%). The results of the publication bias analysis showed the presence of asymmetry in the slope distribution, with no statistical difference. In conclusion, poultry salmonellosis is highly prevalent in Ethiopia. So, it is crucial to increase biosecurity and implement prevention and control methods to safeguard the health of poultry and humans in Ethiopia.